Compassion fatigue among disability camp staff: an exploratory study. Issue 2 (15th March 2017) - Waller, Steven N.; Wozencroft, Angela J.; Scott, Jason L.
ABSTRACT: Being compassionate to others can take its toll on practitioners working in emotionally exhausting professions such as recreational therapy (RT). Research that examines compassion satisfaction/compassion fatigue (CS/CF) in allied health settings is in abundance, but is noticeably absent in RT settings. This paper examines the levels of CS/CF in students working at a therapeutic camp for youth with multiple disabilities in the United States. The findings of the study revealed that: (1) the sample scored in the "high" range on the CS subscale; "average" on the burnout subscale; and "low" in the secondary stress trauma (STS) subscale; and (2) significant differences were found in CS/CF scores based on age and academic major. This research also reveals the importance of training in advance of therapeutic camp experiences towards the end of increasing CS, reducing burnout and STS. The practical implications for students and recreational therapists point to the need for training, awareness of the signs of CF, and the need for effective self-care as strategies.